Didactical philosophy, philosophical didactics – from instrumental rationality to enlightenment? - Wieczerzyński, Mariusz (Hybris, 2017)
The aim of this article is to look at philosophy as a didactic practice in which didactic is seen as critique. Both are immanent to philosophical reflection as a whole. I would like to start with an analysis whether the structure of philosophical thought determines the didactic results (e.g. the Socratic method, philosophy as linguistic competence) and using critical theory I will analyze the possible ways of overcoming instrumental rationality. I will mainly contribute to the works of M. C. Nussbaum. I will then look at the relations between theory and practice, between instrumental and involved, between subjective and objective reason with contributions to M. Horkheimer and T. W. Adorno. The case to consider would be whether teaching philosophy should remain a shallow discipline with only historical approach or can it be presented as a problem-solving device thanks to introducing critical thought. Can it be a remedy to the enlightenment that results in a goal – oriented formal rationality?